Synthesis of 2-N-Salicylidene-5-(substituted)-1,3,4-thiadiazole as Potential Antimicrobial Agents - Salimon, Jumat; Salih, Nadia; Ibraheem, Hanan; Yousif, Emad (Asian Journal of Chemistry, 2010)
Several new 2,5-disubstituted derivatives of 1,3,4-thiadiazoles containing imine moiety were obtained from cyclization of thiosemicarbazide and corresponding p-substituted carboxylic acid in phosphorus oxychloride then the resulted products were reacted with salicylaldehyde to give the final products 3a-h. All the newly synthesized compounds were characterized using FTIR, 1H NMR, 13C NMR and elemental analysis. All compounds have been screened for their antimicrobial activity and showed that the introduction of 1,3,4-thiadiazole ring significantly increase the antibacterial activity